Becoming a STEM-Focused School District: Administrators' Roles and Experiences - Jeanna R. Wieselmann; Gillian H. Roehrig; Elizabeth A. Ring-Whalen; Thomas Meagher (MDPI AG, 2021)
Science, technology, engineering, and mathematics (STEM) schools and districts continue to emerge, and while some research highlights critical components to be included in STEM schools, there is a need to learn more about the process of becoming a STEM school or district. In this study, we investigated a rural United States school district's development and expansion of its STEM education focus, which started in the years leading up to the district's first STEM school opening in 2012. We addressed the research question: How is a district-wide STEM education vision developed, enacted, and sustained by various administrative stakeholders? We interviewed 11 participants, all of whom had some level of administrative responsibility related to the district's STEM mission, coded interviews based on the critical components of STEM schools, and used narrative inquiry methods to describe the district's STEM transition from these administrators' perspectives. Our analysis revealed that several key critical components were central to this district's STEM mission. These components included elements related to leadership, reform-based instructional strategies, and teachers' professional learning. By focusing on different elements at different times and prioritizing several key components throughout, this district was able to achieve its goal of providing STEM instruction to all of the elementary and middle school students.